Impact of reminder module on adherence and treatment outcomes among HIV-positive patients on antiretroviral theraphy in Hospital Sungai Buloh, Malaysia - Abiola, Abdulrahman Surajudeen (2015)
Introduction: Adherence to treatment remains the cornerstone of long term viral suppression and successful treatment outcomes among patients receiving antiretroviral therapy (ART). According to WHO, minimum adherence levels of 95% are required for treatment success. Poor adherence to treatment (clinic visits and medication adherence) remains a stumbling block to the success of treatment programs and generates major concerns about possible resistance of the HIV virus to the currently available ARVs. The objective of this study was to evaluate the impact of a mobile phone reminder module on adherence and treatment outcomes among HIV positive patients on ART in Malaysia. Methods: A single-blinded, parallel group randomized controlled trial conducted in Hospital Sungai Buloh, Malaysia in which 242 Malaysian patients were randomized to intervention or control groups was conducted between January and December, 2014. Intervention consisted of a reminder module delivered through SMS and telephone call reminders by trained research assistants for 24 consecutive weeks, in addition to adherence counseling at every clinic visit. Data on adherence behavior of patients was collected using specialized, pre-validated Adult AIDS Clinical Trial Group (AACTG) adherence questionnaires. Data on weight, clinical symptoms, CD4 count and viral load tests were also collected. Data was analyzed using SPSS version 21 and R software. A 5% level of statistical significance was considered for all analysis. Repeated measures ANOVA, Friedman’s ANOVA and Multivariate regression models were used to evaluate efficacy of the intervention as well as to establish the relationship between the independent (predictors) and outcome variables. Results: The response rate after 6 months follow up was 93%. There were no significant differences at baseline in gender, employment status, income distribution and residential location of respondents between the intervention and control group. After 6 months follow up, the mean adherence was significantly higher in the intervention group as compared to the control group. The proportion of respondents ii who had good (>95%) adherence was significantly higher in the intervention group. A significantly lower frequency in missed appointments (p=0.001), lower viral load (p=0.001), higher rise in CD4 count (p=0.017), lower incidence of tuberculosis (p=0.001) and OIs (p=0.001) at 6 months follow up, was observed among patients in the intervention group. We found that both medication adherence and clinic attendance significantly predicts immunological and virological outcomes of antiretroviral therapy. Conclusion: The findings of the current study indicates that mobile phone reminders are effective in improving adherence (clinic attendance and medication adherence) and treatment outcomes (immunological and virological) among HIV positive patients on ART. The ubiquitous nature of mobile phones even among HIV positive patients from low to middle income countries provides an excellent platform for targeted health interventions, irrespective of the nature of the epidemic, whether concentrated or generalized. Since the success of ART programs is largely measured by retention on treatment, the potential effects of this intervention in tracking patient’s clinic attendance and ensuring that they are retained in care remains of immense value in HIV programming.